Business Model among Home Industries in Kulon Progo - Pinjung Nawang Sari; Jumeri Jumeri; Filigon Adiguna Puspoyudo (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2018)
Business model is a system of resources and activities, which create a value that is useful to the customer and the sale of this value makes money for the company. The purpose of the analysis of business models is to deepen and broaden the knowledge about basic components of a business model. The Business Model Canvas (BMC) is a tool that provides a clear view of what the company needs to achieve and focuses on the strategic elements that matter most and will have the greatest impact to the business. This paper discuss about BMC among home industries in Kulon Progo Regency, based on their products: “pong” tofu, white tofu, traditional snacks, various kind of “peyek”, dan various kind of tempeh (soybean, “gembus”, and “benguk”). These five home industries compared among the nine building blocks in the BMC: customer segments, customer relationships, distribution channels, value proposition, key resources, key activities, partners, cost structure and revenue streams. BMC helps the home industries in creating their business models based on nine building blocks. Discussion among these home industries in Kulon Progo Regency was being conducted in order to help the entrepreneurs to use these models in the right way‚ and successfully plan their future business.